The Time‐Varying Price of Financial Intermediation in the Mortgage Market - FUSTER, ANDREAS; LO, STEPHANIE H.; WILLEN, PAUL S. (Journal of Finance, 2024)
ABSTRACT We introduce a new measure of the price charged by financial intermediaries for connecting mortgage borrowers with capital market investors. Based on administrative lender pricing data, we document that the price of intermediation reacts strongly to variation in demand, reflecting capacity constraints of mortgage originators. This positive comovement of price with quantity reduced the pass‐through of quantitative easing. We also find a notable upward trend in this price between 2008 and 2014, likely due to increased legal and regulatory burden in the mortgage market. The trend led to an implicit cost to borrowers of nearly $100 billion over this period.